2014
DOI: 10.2147/ijnrd.s65929
|View full text |Cite
|
Sign up to set email alerts
|

B-type (brain) natriuretic peptide and pruritus in hemodialysis patients

Abstract: Introduction and objective:While pruritus is a common complication in hemodialysis patients, the pathophysiological mechanisms remain obscure. Recently, B-type (brain) natriuretic peptide (BNP) has been defined as an itch-selective neuropeptide in pruriceptive neurons in mice, and higher serum levels of BNP are frequently observed in hemodialysis patients. The objective of the present study was to evaluate the role of serum BNP in pruritus in patients undergoing hemodialysis. Patients and methods:The current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Therefore, the increase of BNP with volume overload may have a role in itching transmission. Clinically, Shimizu et al reported an association between elevated BNP and the severity of pruritus [ 41 ]. This provides a possible link between pruritus and volume overload in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increase of BNP with volume overload may have a role in itching transmission. Clinically, Shimizu et al reported an association between elevated BNP and the severity of pruritus [ 41 ]. This provides a possible link between pruritus and volume overload in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that BNP-NPRA signaling is a key mechanism of itch transmission in the mouse spinal cord (Mishra and Hoon, 2013). In addition, an increased level of serum BNP was found to be associated with the degree of pruritus in hemodialysis patients (Shimizu et al, 2014). Anatomic and pharmacological studies have demonstrated that GRP-GRPR system acts downstream of the BNP-NPRA signaling in the pruriceptive circuit as an itchselective regulation by BNP (Mishra and Hoon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…BNP knocked out mice lose almost all behavioral responses to itchinducing agents [26]. Shimizu et al also demonstrated that serum brain BNP associates with the pruritus of hemodialysis patients [27]. Uremic pruritus might be a consequence of elevation of BNP induced by left ventricular pressure and volume overload due to salt and water retention and anemia, and increased blood volume and left ventricular end diastolic dysfunction caused by the arteriovenous vascular access in hemodialysis patients [28][29][30].…”
Section: Discussionmentioning
confidence: 99%